1982
DOI: 10.1002/1097-0142(19821201)50:11<2496::aid-cncr2820501140>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up study on gastric adenoma and its relation to gastric protruded carcinoma

Abstract: A total of 191 gastric adenomas in 178 patients was studied macroscopically by endoscopy and histopathologically by endoscopic biopsy. Among the lesions, 85 in 74 patients were followed‐up for six months to 12 years. Gastric adenomas were found to be more frequent in the aged, with a rate of 0.1% in the third decade but 3.7% in the ninth decade, on gastroscopic examination. Gastric cancers coexistent with the gastric adenomas were seen in 14 cases (8%), and were more frequent in male than in female patients (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 6 publications
2
61
0
Order By: Relevance
“…However, in Japan, it is known that gastric adenoma is not a precursor lesion of early gastric carcinoma. 31 Thus, we believe that the intestinal phenotype of early gastric cancers does not derive from gastric adenoma. We suggest that intestinal-phenotype cancers have genetic profiles that set the cells on different pathways from those leading to the development of gastric adenomas, although both tumors may share common genetic alterations in their initial tumorigenesis.…”
Section: Genetic Profiles Of Adenocarcinomasmentioning
confidence: 94%
“…However, in Japan, it is known that gastric adenoma is not a precursor lesion of early gastric carcinoma. 31 Thus, we believe that the intestinal phenotype of early gastric cancers does not derive from gastric adenoma. We suggest that intestinal-phenotype cancers have genetic profiles that set the cells on different pathways from those leading to the development of gastric adenomas, although both tumors may share common genetic alterations in their initial tumorigenesis.…”
Section: Genetic Profiles Of Adenocarcinomasmentioning
confidence: 94%
“…In the gastric adenoma-carcinoma sequence, TGF-␤ RII gene mutation occurred early in the adenoma stage and it persisted after malignant transformation. (Lab Invest 2000, 80:57-64).G astric adenoma is a precancerous lesion, 11% to 40% of which transforms into carcinoma (Kamiya et al, 1982;Ming and Goldman, 1965). The intestinal type of gastric carcinoma is different from the diffuse type in patterns of histopathology and genetic alterations.…”
mentioning
confidence: 99%
“…[1][2][3] This discrepancy between forceps biopsy samples and post-resection specimens is likely unavoidable and an inevitable limitation of forceps biopsy, due to the small amount of tissue sampled. [4][5][6]17 In this investigation, which was based on white light endoscopic images, we found that some specimen features, including size of 15 mm or greater, depressed appearance, central concavity, and nodular surface, were useful for predicting carcinoma as a final diagnosis in FBP adenomas, regardless of histologic grades.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Accurate diagnosis and classification of epithelial neoplasms requires whole specimens; this discrepancy is therefore inevitable, as forceps biopsies obtain only small parts of the entire lesion. [4][5][6] Recent research has shown that advanced endoscopic imaging technology may be useful in diagnosing gastric epithelial neoplasm more precisely before dissection.…”
Section: Introductionmentioning
confidence: 99%